ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT FERTILITAS DI KOTA PARIAMAN - Fahriat Yulzain (Universitas Negeri Padang, 2017)
: Increase of population will in indirectly cause the effect, either positive or negative effects. Increase of population in Pariaman City caused by high levels of fertility. The purpose of this research is to analyze the factors which affect the fertility in Pariaman City. Based on the result of research show that there is a negative significant relation of first age marriage (X1) with fertility, there is a negative significant relation of level of maternal education (X2) with fertility. And there is a positive not significant relation of employment maternal status (X3) with fertility, relation of level of income (X4) with fertility is a positive not significant. Relation of Education level head of household (X5) with fertility is a positive not significant. And there is a positive significant relation of field efforts of the head of household (X6) with fertility. So based on the results of research required make sure increased education and income - generating job, a better and more adequate field efforts in Pariaman City so that all family members can acquire a decent life and health.